Four new African turriform gastropods (Mollusca: Conoidea) - Morassi, Mauro; Bonfitto, Antonio (Zootaxa, 2013)
Four new species, belonging to four distinct conoidean families, are described from east Africa and Mozambique Channel. Iredalea adenensis sp. nov. (Drilliidae Olsson, 1964), from Gulf of Aden, and Buchema shearmani sp. nov. (Horaiclavidae Bouchet et al., 2011), from off Mogadishu (Somalia), both trawled by local fishermen, represent the first record of their respective genera in eastern Africa. Crassispira somalica sp. nov. (Pseudomelatomidae Morrison, 1965), also collected offshore from Modagishu (Somalia), represents the first eastern Africa species bearing “typical” Crassispira features. Tropidoturris vizcondei sp. nov. (Borsoniidae Bellardi, 1875), from the Mozambique Channel, increases the knowledge of a genus considered endemic to southeastern Africa.